Pemanfaatan Kulit Jagung sebagai Bioadsorben untuk Meregenerasi Minyak Goreng Bekas - Umi Fathanah; Mirna Rahmah Lubis (Fakultas Teknik, 2022)
Cooking oil is a food processing medium that is often used by various levels of society for cooking needs. People’s habit of using cooking oil repeatedly at high temperatures will cause damage to the oil so that it greatly affects the nutrition and quality of processed foods. For this reason, it is very important to make efforts to regenerate cooking oil that has been used repeatedly with a safer process. Corn husks can be used as a bioadsorbent to regenerate used cooking oil. The purpose of this study was to investigate the effect of adding bioadsorbent from corn husks on the acquisition of moisture content, free fatty acids (FFA), and peroxide number. 200 ml of used cooking oil was contacted with corn husk bioadsorbent with the addition of 1, 5, and 10 grams of bioadsorbent and contact times of 30, 60, and 90 minutes. Furthermore, used cooking oil that has been regenerated was analyzed for moisture content, FFA, and peroxide number. The results showed that 10 grams of bioadsorbent with a contact time of 90 minutes had a moisture content of 0.15%, FFA 0.11%, and a peroxide number of 1.15 meq/kg, which met the cooking oil quality standard (SNI 3741-1995).